2010
DOI: 10.1111/j.1468-0475.2009.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Are All Professional Investors Sophisticated?

Abstract: Existing empirical evidence is inconclusive as to whether professional investors show more sophisticated behavior than individual investors. Therefore, we study two important groups of professional investors and compare them with laymen by means of a survey covering about 500 investors. We find that some professionals, i.e. institutional investors, behave in a more sophisticated manner than laymen, whereas the less researched investment advisors seem to do even worse. Our survey approach complements available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 60 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…Previous research showed that the predictions of financial professionals in the investment field were rather inaccurate and excessively optimistic (Shiller, 2000;Abarbanell & Lehavy, 1993;Kothari, 2001;Bradshaw, 2011;DeBondt & Thaler, 1990;Easterwood & Nutt, 1999). Moreover, it was shown that professionals were sometimes more inaccurate than the lay people (Staël von Holstein, 1972;Yates, McDaniel, & Brown, 1991;Menkhoff, Schmeling, & Schmidt, 2013;Glaser, Langer, & Weber, 2005). According to these findings, we hypothesized that group of financial professionals would be excessively optimistic in predicting future returns of stock indices.…”
Section: The Present Studymentioning
confidence: 85%
See 4 more Smart Citations
“…Previous research showed that the predictions of financial professionals in the investment field were rather inaccurate and excessively optimistic (Shiller, 2000;Abarbanell & Lehavy, 1993;Kothari, 2001;Bradshaw, 2011;DeBondt & Thaler, 1990;Easterwood & Nutt, 1999). Moreover, it was shown that professionals were sometimes more inaccurate than the lay people (Staël von Holstein, 1972;Yates, McDaniel, & Brown, 1991;Menkhoff, Schmeling, & Schmidt, 2013;Glaser, Langer, & Weber, 2005). According to these findings, we hypothesized that group of financial professionals would be excessively optimistic in predicting future returns of stock indices.…”
Section: The Present Studymentioning
confidence: 85%
“…Some of the research on predicting future equity returns found that forecasts of financial professionals are often more inaccurate compared to the lay people (Staël von Holstein, 1972;Yates, McDaniel, & Brown, 1991;Menkhoff, Schmeling, & Schmidt, 2013;Glaser, Langer, & Weber, 2005). They hypothesized about an inverse effect of expertise in explaining this paradox.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations